Challenges in Teaching IELTS for Police Academy Alums at Police Language School - Firza Garuda; Zukfa Sakhiyya (Universitas Islam Negeri Palopo, 2025)
This qualitative case study examines the pedagogical challenges faced within the International English Language Testing System (IELTS) preparation program at the Police Language School (Sebasa), with a specific focus on the instruction of Police Academy graduates. Data were collected through semi-structured interviews and classroom observations involving eight instructors, comprising two representatives from each of the IELTS modules (Listening, Reading, Writing, and Speaking). The thematic analysis reveals that the primary challenge is a